The safety and efficacy of neoadjuvant immunochemotherapy in locally advanced esophageal squamous cell carcinoma: a meta-analysis and systematic review - Shen, Qing; Liu, Haiyang; Xue, Huimin; Yilixiati, Ailifeiya; Yan, Senmiao; Li, Wenya; Song, Na (Frontiers in Immunology, 2026)
PurposeThe standard treatment for locally advanced esophageal squamous cell carcinoma (ESCC) is neoadjuvant chemoradiotherapy plus esophagectomy; however, there remains a significant risk of distant metastasis following surgery, which compromises long-term survival among patients. The present study involved a meta-analysis designed to explore the safety and efficacy of neoadjuvant immunochemotherapy (nICT) in patients with locally advanced ESCC.MethodsPubMed, Embase, The Cochrane Library, and Web of Science were searched from inception until June 30, 2025. The extracted data included: pathological complete response (pCR), major pathological response (MPR), objective response rate (ORR), R0 resection rate, the incidence of adverse events (AEs), and ≥ Grade 3 AEs.ResultsSome 30 studies with a total of 1185 patients were included, wherein the treatment regimen was nICT, without restrictions on the type of immune agents. The results showed that the MPR rate after nICT was 53% (95% confidence interval (CI): 46-59%), and the pooled pCR rate was 32% (95% CI: 29-35%). The pooled R0 resection was 97% (95% CI: 96-98%), and the pooled ORR rate was 68% (95% CI: 64-72%). The incidence of ≥ Grade 3 treatment-related adverse events (TrAEs) was 26% (95% CI: 17-38%), the incidence of ≥ Grade 3 surgery-related adverse events (SrAEs) was 3% (95% CI: 1-5%), and the main TrAEs in hematological toxicity were leukopenia, neutropenia, and thrombocytopenia. The main symptoms of non-hematological-toxicity TrAEs were nausea, vomiting, fatigue, decreased appetite, and rash. Infection and anastomotic fistula were the most common postoperative complications. In all, 9 cases of surgery-related deaths were identified. Among them, 3 cases were pulmonary complications (all related to pneumonia), 3 cases were direct surgery-related complications (hemorrhagic shock, anastomotic leakage complicated with hemorrhage, and esophagotracheal fistula, respectively), 1 case was severe infection, and 2 cases were attributed to unspecified causes (fatal due to surgery-related Grade V adverse events). Fatal surgical complications were uncommon.ConclusionsThis study preliminarily indicates the efficacy and safety of nICT in locally advanced ESCC in China. This combination regimen exhibits superior pCR with tolerable safety profiles, suggesting a new therapeutic strategy for patients with locally advanced ESCC. (CRD42024574607).Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024574607, identifier CRD42024574607.